Creativity of Ashugs: An Investigation on Ashug Culture in Azerbaijan - Ilshatovna, Galyautdinova Gulshat; Ihsanovna, Mingazova Liailia; Amiruglu, Sayilov Galib (Journal of History Culture and Art Research, 2017)
Ashug art forming one of the fundamental, private branches of Azerbaijan folklore is the actual problem of modern folklore-study investigating ashug sphere, schools and artisans. Ashug is the event of folk activity existing in ancient times with different names. In the structure of this tradition the important historical layers of the folk culture as the ancient cult, belief, art find its reflection. Shirvan is one of the ancient culture centers which has its own historical evolution and development stages. Shirvan had historical relations with the developed cultural states of the ancient world and was acquainted with main achievements of East and West culture. Azerbaijan ashug poem of the 19th century was significant with the important event. The performance style of woman masters appeared in ashug activity. For the first time this tradition showed itself in Shirvan, then it spread in other ashug spheres. The woman ashugs in Shirvan had different characters than other ashugs. They were the masters displaying interest to the folk poem, knowing the classic style, creating gazal and gasidas in Aruz meter (classical poetic meter in oriental poetry) and writing some poems in such style. Shirvan sphere and Shirvan ashug activity saving the richest examples of Azerbaijan culture and folklore, at the same time different ashug masters of Shirvan region haven’t been the system subject of the investigation. We can meet the thoughts and considerations about Shirvan folklore sphere and the life of different ashugs in the limited works. But in the new period the place and the role of ashug in the ashug culture and folklore tradition haven’t been cleared up.